2020
DOI: 10.21203/rs.3.rs-48700/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MECP2 promotes migration and invasion of gastric cancer cells via modulating the Notch1/c-Myc/mTOR signaling pathways by suppressing FBXW7 transcription

Abstract: Background: Methyl-CpG-binding protein 2 (MECP2), an epigenetic regulatory factor, promotes the carcinogenesis and progression of a number of cancers. However, its role in the migration and invasion of gastric cancer (GC) as well as the underlying molecular mechanisms remain unclear.Methods: Immunohistochemistry (IHC), Western blot, and quantitative real-time PCR (qRT-PCR) were performed to measure the expressions of MECP2, FBXW7, c-Myc, mTOR and Notch1 in GC tissues and cell lines, respectively. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In addition, extracellular matrix structures such as perineuronal nets (PNNs), which cover neuronal cell bodies, are more abundant in RTT as compared to healthy brains. , This could be due to disrupted gene expressions of collagens and downregulated COL19A1. The regulatory role of MECP2 on genes involved in processes such as neuronal development, differentiation and signal transduction has been clearly seen. PNNs of parvalbumin-positive (PV+) cells are particularly effective in neuronal cell differentiation . Differentiation in the OTX2 gene located in the PNNs of PV+ cells could be another factor affecting PNN dysregulation in RTT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extracellular matrix structures such as perineuronal nets (PNNs), which cover neuronal cell bodies, are more abundant in RTT as compared to healthy brains. , This could be due to disrupted gene expressions of collagens and downregulated COL19A1. The regulatory role of MECP2 on genes involved in processes such as neuronal development, differentiation and signal transduction has been clearly seen. PNNs of parvalbumin-positive (PV+) cells are particularly effective in neuronal cell differentiation . Differentiation in the OTX2 gene located in the PNNs of PV+ cells could be another factor affecting PNN dysregulation in RTT.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, researchers found that MeCP2 inhibited FBXW7 expression in GC cells by binding to methylated CpG sites in the FBXW7 promoter, playing important roles in blocking cell migration and invasion. Reduced FBXW7 expression activated the Notch1/c-Myc/mTOR signaling pathways, and promoted GC cells migration and invasion [118].…”
Section: Mecp2 and Gastric Cancermentioning
confidence: 98%
“…Methyl-CpG-binding protein 2 (MECP2), an epigenetic regulatory factor, promotes the carcinogenesis and progression of a number of cancers. Zhao et al found that MECP2 could regulate the Notch1/C-MYC/mTOR signaling pathway by inhibiting FBXW7 transcription, thereby promoting GC cell migration and invasion 114 . The catalytically inactive pseudophosphatase serine/threonine/tyrosine interacting protein (STYX) is a member of the protein tyrosine phosphatase family.…”
Section: Key Molecules Regulating F-box Proteins In Gastric Cancermentioning
confidence: 99%